Evaluating the Quality Of E-Courses from The Students Perception and E-course Quality Evaluation Metrics (DAU- EQEM) at Dar Al Uloom University - Evan Asfoura, Mohammad Samir Abdel-Haq, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
E-learning and e-courses have received great practical and research interest during the previous years. Recently, there has been a growing interest in increasing efficiency and adherence to quality standards for e-learning and e-courses. With the restrictions imposed by the recent COVID-19 pandemic and the shift to reliance on e-learning and e-courses, this has increased the interest of higher education institutions, especially in the Kingdom of Saudi Arabia, Dar Al-Uloom University has developed a framework to ensure the quality of electronic and electronic learning courses DAU-EQEM The framework consists of eight standards, And that was applied through this study on 272 electronic courses distributed over three colleges in addition to the university preparation program at Dar Al Uloom University. To verify the evaluation results, the evaluation results were matched with the results of a survey of students' perception at the university about the quality of e-courses. The questionnaire consists of 5 themes and 25 items. The results showed a great convergence in the results of the evaluation tools used to verify the quality of electronic courses at Dar Al Uloom University. The results also showed an advanced level of quality of e-courses at Dar Al Uloom University, with the need to develop plans to ensure continuous improvement and raise the level of performance related to the e-learning system and its e-courses.